Thermal and Mechanical Properties of Poly(L-Lactic Acid) Composities Based on Sodium Alginate - Zhao, Li-Sha; Cai, Yan-Hua (Asian Journal of Chemistry, 2013)
The melting behaviour at different conditions, thermal stability and mechanical properties of poly(L-lactic acid)/sodium alginate (PLLA/SA) composities were investigated. The results showed that the melting behaviour was affected by heating rate, crystallization temperature and crystallization time and the double melting peaks is in accord with the melting recrystallization and remelting process. Meantime, the melting behaviour also further confirmed that sodium alginate could improve the crystallization of PLLA. Thermal stability of PLLA composities indicated that PLLA decomposed fast and completed in one stage above 300 ºC and the decomposition process of PLLA/2%SA composities was similar to that of PLLA, but the onset decomposition temperature was lower than that of PLLA. Upon addition of 2 % sodium alginate, comparing with the neat PLLA, the tensile strength and modulus increase from 49.8 Mpa and 2329.4 Mpa to 72.7 Mpa and 3434.5 Mpa. However, the elongations at break of PLLA/2%SA composities decreased from 2.89 to 2.15 %.